Aset Tak Berwujud Dalam Nilai Yang Nyata: Peran Intellectual Capital Terhadap Nilai Perusahaan - Muhammad Raihan Mubaraq; Hamidah Muslimah (Jurnal Riset Mahasiswa Akuntansi, 2026)
This study aims to analyze the effect of intellectual capital on firm value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. This research uses a quantitative approach with a causal research design. The population in this study consists of all food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research sample was determined using the purposive sampling technique based on specific criteria to 100 observes obtain companies that align with the research. The data used in this study are secondary data obtained from companies’ financial statements. The data analysis method employed is Partial Least Square (PLS) with the assistance of SmartPLS 4 software. The stages of analysis include descriptive statistics, outer model analysis, inner model analysis, and hypothesis testing. The results show that intellectual capital has a positive and significant effect on firm value. This finding indicates that companies with better management of intellectual capital tend to have higher firm value, as reflected in increased investor confidence in the company’s future prospects.